2011
DOI: 10.14742/ajet.955
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative or collaborative literacy practices: Mapping metadiscourse in a business students' wiki group project

Abstract: <span>Although wikis have been used successfully in collaborative learning in higher education, there is a lack of research investigating wikis in business module assessment tasks. Little research to date has been conducted on how wikis formatively develop international English as a second language (ESL) in business students' academic discourse. In this case study, students' use of a wiki in an assessment task in the </span><em>Intermediate Financial Reporting</em><span> (IFR) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
2
26
0
1
Order By: Relevance
“…In Alyousef and Picard's (2011) study, groups of English as a Second Language (ESL) university students were required to read a scenario, answer questions through the wiki discussion pages, and then create a final report on the wiki page. Alyousef and Picard found that ''most students' collaborations were not true since they were not engaged in co-authoring, but rather providing feedback to each other'' (op.…”
Section: Nature Of the Tasksmentioning
confidence: 99%
“…In Alyousef and Picard's (2011) study, groups of English as a Second Language (ESL) university students were required to read a scenario, answer questions through the wiki discussion pages, and then create a final report on the wiki page. Alyousef and Picard found that ''most students' collaborations were not true since they were not engaged in co-authoring, but rather providing feedback to each other'' (op.…”
Section: Nature Of the Tasksmentioning
confidence: 99%
“…There is, to the best of my knowledge, a lack of research investigating metadiscourse features in multimodal budgeting reports that encompass tables and graphs. With the exception of Alyousef and Picard's (2011) study, no other investigations have been made in exploring the use of metadiscourse features in tertiary multimodal business courses. Garzone (2009) noted that "so far, contributions from linguists specifically dealing with multimodality in business discourse have been relatively few " (p. 156).…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative learning means that the tasks are done together whereas cooperative learning means that the tasks are divided between learners (Alyousef & Picard, 2011). Collaborative writing is widely recognised as a central component of classroom learning by researchers in the field of L2 writing (e.g.…”
Section: Introductionmentioning
confidence: 99%